2020
DOI: 10.25259/sni_287_2020
|View full text |Cite
|
Sign up to set email alerts
|

Isolated painless scoliosis in lumbar disc herniation

Abstract: is is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-Share Alike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although most patients with LDH have typical clinical features, such as lower back pain, sciatica, and positive straight leg raising test, some patients do not have these features. Akhaddar et al 10 reported a case of LDH with isolated painless scoliosis. Zhu et al 11 reported that 4 of 29 adolescents with LDH who had a scoliotic posture were misdiagnosed with idiopathic scoliosis at the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients with LDH have typical clinical features, such as lower back pain, sciatica, and positive straight leg raising test, some patients do not have these features. Akhaddar et al 10 reported a case of LDH with isolated painless scoliosis. Zhu et al 11 reported that 4 of 29 adolescents with LDH who had a scoliotic posture were misdiagnosed with idiopathic scoliosis at the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%